Correlation between management and leadership competencies and sustainability measures in Jordanian governmental hospitals: managers’ perception - Allari, Rabia S.; Abu-Dames, Mustafa (Frontiers in Sustainability, 2025)
IntroductionDeveloping a new model for the healthcare system that includes a set of management and leadership competencies is crucial to the improvement of productivity and sustainability of organizations.ObjectiveThis study aims to identify the management and leadership competencies and sustainability measures from the perspective of Jordanian managers in governmental hospitals.MethodsA descriptive correlational study design was utilized. A convenient sampling method was used to select managers in governmental hospitals in the Central region of Jordan. A self-administered questionnaire was conducted using the Management and Leadership Questionnaire (MLQ30) and the Sustainability in Healthcare Questionnaire (SHQ).ResultsThe total mean score of the management and leadership scale was 3.49. The highest-ranked items were “Speaking confidently and presenting to groups” and “Building trust and modeling integrity “. while the lowest-ranked items are “Thinking and managing globally” and “Creating and innovating.” The importance of sustainability measures is ranked as follows: social, environmental, and economic factors. There was a positive, statistically significant relationship between managers’ competencies and the importance of sustainability measures. The combined competencies can predict the application of sustainability measures.ConclusionThe sustainability factor that has been found exhibits components of environmental, economic, and social dimensions and this aligns well with the literature. Future hospital managers are today’s students, and the job they do will either positively or negatively affect their institutions whether governmental or private, and society. So, including core competencies of management and leadership that foster sustainable development in the curricula might be a significant step toward integrating sustainability in higher education, among other activities.